Pathology Associated With Streptococcus spp. Infection in Baboons (Papio spp.). Issue 5 (September 2020) - Davis, Katelin L.; Gonzalez, Olga; Kumar, Shyamesh; Dick, Edward J.
Streptococcus spp. are a source of morbidity and mortality in captive nonhuman primate populations. However, little is known about the lesions associated with naturally occurring streptococcal infections in baboons ( Papio spp.). The pathology database of the Southwest National Primate Research Center was searched for all baboon autopsies from 1988 to 2018 in which Streptococcus spp. were cultured. Baboons on experimental protocol were excluded. The gross autopsy and histopathology reports were reviewed. Archived specimens were retrieved and reviewed as needed for confirmation or clarification. Fifty-six cultures were positive for Streptococcus spp. in 54 baboons with evidence of bacterial infection. Associated gross lesions included purulent exudate, fibrinous to fibrous adhesions, hemorrhage, mucosal thickening, organomegaly, and abscessation. Histologic lesions included suppurative inflammation, abscessation, necrosis, hemorrhage, fibrin accumulation, and thrombosis. Lungs and pleura ( n = 31) were the most commonly infected organ followed by the central nervous system ( n = 16), spleen ( n = 15), soft tissues ( n = 12), air sacs, liver, peritoneum, adrenal glands, heart, lymph nodes, uterus, kidneys, biliary system, bones, ears, umbilical structures, mammary glands, pancreas, placenta, and salivary glands. Infections by non-β-hemolytic Streptococcus spp. predominated in the lungs and air sacs; the most common isolate was Streptococcus pneumoniae . Infections by β-hemolytic Streptococcus spp. predominated in the soft tissues and reproductive tract. Naturally occurring β-hemolytic and non-β-hemolytic Streptococcus spp. infections cause morbidity and mortality in captive baboon populations. The lesions associated with streptococcal infection are similar to those reported in human infection. Thus, the baboon may represent an underutilized model for studying Streptococcus spp. as pathogens.